2021
DOI: 10.1021/acs.est.1c01016
|View full text |Cite
|
Sign up to set email alerts
|

Iron Minerals Mediated Interfacial Hydrolysis of Chloramphenicol Antibiotic under Limited Moisture Conditions

Abstract: Iron minerals are important soil components; however, little information is available for the transformation of antibiotics on iron mineral surfaces, especially under limited moisture conditions. In this study, we investigated the catalytic performance of four iron minerals (maghemite, hematite, goethite, and siderite) for the hydrolysis of chloramphenicol (CAP) antibiotic at different moisture conditions. All the iron oxides could efficiently catalyze CAP hydrolysis with the half-lives <6 days when the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…2c, d ). The excessive surface water molecules would compete for the reactive sites 10 , 12 , and reduce the Lewis acidity of the exposed Fe (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2c, d ). The excessive surface water molecules would compete for the reactive sites 10 , 12 , and reduce the Lewis acidity of the exposed Fe (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…PAEs are hydrolysable, however, at slow hydrolysis rates with the hydrolysis half-lives ( t 1/2 ) even up to several years under neutral pH conditions 9 . In our previous studies, we found that chloramphenicol antibiotic could be rapidly hydrolyzed by clay minerals and iron oxides under limited surface moisture conditions, attributing to the strong Brønsted-/Lewis-acidities of the dry mineral surface 10 12 . By contrast, under water-oversaturated conditions, the surface reactions were completely suppressed due to the shielding effect of surface water layers 10 12 .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Residues of pollutants such as CAP in medical wastewater adversely affect human health . CAP is often used in pharmaceutical and aquaculture industries as a broad-spectrum antibacterial antibiotic. , The increasing use of CAP , has resulted in CAP residues being found in aquatic environments and animals. CAP is banned in many countries because it can cause aplastic anemia and leukemia after entering the human body .…”
Section: Introductionmentioning
confidence: 99%